Healthcare for migrant workers in destination countries: a comparative qualitative study of China and Malaysia. Issue 12 (2nd December 2020) - Loganathan, Tharani; Rui, Deng; Pocock, Nicola Suyin
Abstract : Objectives: This paper explores policies addressing migrant worker's health and barriers to healthcare access in two middle-income, destination countries in Asia with cross-border migration to Yunnan province, China and international migration to Malaysia. Design: Qualitative interviews were conducted in Rui Li City and Tenchong County in Yunnan Province, China (n=23) and Kuala Lumpur, Malaysia (n=44), along with review of policy documents. Data were thematically analysed. Participants: Participants were migrant workers and key stakeholders with expertise in migrant issues including representatives from international organisations, local civil society organisations, government agencies, medical professionals, academia and trade unions. Results: Migrant health policies at destination countries were predominantly protectionist, concerned with preventing transmission of communicable disease and the excessive burden on health systems. In China, foreign wives were entitled to state-provided maternal health services while female migrant workers had to pay out-of-pocket and often returned to Myanmar for deliveries. In Malaysia, immigration policies prohibit migrant workers from pregnancy, however, women do deliver at healthcare facilities. Mandatory HIV testing was imposed on migrants in both countries, where it was unclear whether and how informed consent was obtained from migrants. Migrants who did not pass mandatory health screenings in Malaysia would runaway rather than be deported and become undocumented in the process. Excessive attention on migrant workers with communicable disease control campaigns in China resulted in inadvertent stigmatisation. Language and financial barriers frustrated access to care in both countries. Reported conditions of overcrowding and inadequate healthcare access at immigration detention centres raise public health concern. Conclusions: This study's findings inform suggestions to mainstream the protection of migrant workers' health within national health policies in two middle-income destination countries, to ensure that health systems are responsive to migrants' needs as well as to strengthen bilateral and regional cooperation towards ensuring better migration management.